Correlation between transvaginal sonographic evaluation of adenomyosis and histopathological outcomes - Towhid Hossain, M.; Begum, Morshida; Ali Kabir, M.; Mahbub, Abrar; Kamal, Mahmud H. M.; Kulsum, Syeda U.; Sultana, Nasim; Deepa, Zereen S.; Nazlee, Farah (International Journal of Research in Medical Sciences, 2025)
Background: Transvaginal sonography is a popular method to diagnose adenomyosis, leiomyoma and other pathology of uterus which ultimately lead to hysterectomy operative procedure. This prospective study was conducted in the Department of Radiology and Imaging, Bangabandhu Sheikh Mujib Medical University (BSMMU) to evaluate the accuracy of various transvaginal ultrasonographic findings (TVS) in the diagnosis of adenomyosis with correlation of histopathological results. Methods: One hundred and forty patients scheduled for hysterectomy also selected for preoperative transvaginal sonography. All sonographic findings were compared with the histopathological results. Results: The prevalence of adenomyosis was 37.1%. The sensitivity and specificity of these results were 80.8% and 61.4%. The positive (PPV) and negative (NPV) predictive values were 55.3% and 84.4%. Diagnostic accuracy by transvaginal sonography for adenomyosis was 68.6%. The highest accuracy for the diagnosis of adenomyosis was globular appearing uterus, subendometrial echogenic linear striations and myometrial cysts. In the diagnosis of adenomyosis among transvaginal ultrasound findings, the subendometrial linear striations had the highest diagnostic accuracy. Heterogeneous myometrium was the most common in patients with adenomyosis but with poor specificity. The most specific sonographic features were (95.5%) in the subendometrial linear striations which also had the highest PPV (80.0%) for the diagnosis of adenomyosis. All the results have been supported by statistical tests. Conclusions: Transvaginal ultrasound technique proved to be the very good diagnostic tools for the diagnosis of adenomyosis.